3-(2H-Tetrazol-5-yl)pyridinium trifluoroacetate - Li Zhang (Acta Crystallographica Section E, 2009)
In the cation of the title compound, C6H6N5+·CF3COO−, the pyridine and tetrazole rings are nearly coplanar, making a dihedral angle of 2.49 (19)°. In the crystal, the cations and anions are connected by intermolecular N—H...O and N—H...(F,O) hydrogen bonds, forming centrosymmetric [2 + 2] aggregates, which stack along the a axis.